2020
DOI: 10.1038/s41467-020-20160-w
|View full text |Cite
|
Sign up to set email alerts
|

Optogenetic stimulation of the liver-projecting melanocortinergic pathway promotes hepatic glucose production

Abstract: The central melanocortin system plays a fundamental role in the control of feeding and body weight. Proopiomelanocortin (POMC) neurons in the arcuate nucleus of the hypothalamus (ARC) also regulate overall glucose homeostasis via insulin-dependent and -independent pathways. Here, we report that a subset of ARC POMC neurons innervate the liver via preganglionic parasympathetic acetylcholine (ACh) neurons in the dorsal motor nucleus of the vagus (DMV). Optogenetic stimulation of this liver-projecting melanocorti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 57 publications
(132 reference statements)
4
26
0
Order By: Relevance
“…The improved glucose tolerance in mice by lorcaserin was found to be mediated by reducing the hepatic glucose production and improving glucose disposal, without change of insulin secretion ( 65 ) ( Table 1 and Figure 2 ). Interestingly, a recent study showed that a subset of POMC neurons may have the ability to promote hepatic glucose production, which was speculated to be relevant with the heterogeneity of POMC neurons ( 68 ). Given the complex functions of POMC neurons in the brain, the relationship between this subset of POMC neurons and POMC 5-HTR2C neurons remains to be further elucidated.…”
Section: Glucose Homeostasismentioning
confidence: 99%
“…The improved glucose tolerance in mice by lorcaserin was found to be mediated by reducing the hepatic glucose production and improving glucose disposal, without change of insulin secretion ( 65 ) ( Table 1 and Figure 2 ). Interestingly, a recent study showed that a subset of POMC neurons may have the ability to promote hepatic glucose production, which was speculated to be relevant with the heterogeneity of POMC neurons ( 68 ). Given the complex functions of POMC neurons in the brain, the relationship between this subset of POMC neurons and POMC 5-HTR2C neurons remains to be further elucidated.…”
Section: Glucose Homeostasismentioning
confidence: 99%
“…8,46 Given our findings, both GE and GI should promote a decrease in glycemia. However, recent literature indicated that AgRP neuronal activation or inhibition is not associated with a change in peripheral glucose levels, 47,48 although it may change insulin sensitivity. 49,50 On the other hand, surprisingly, inhibiting and exciting POMC neurons is related to an increase in glucose, 47,48 indicating that POMC neurons are involved in adapting glycemia to the time of the day.…”
Section: Discussionmentioning
confidence: 99%
“…However, recent literature indicated that AgRP neuronal activation or inhibition is not associated with a change in peripheral glucose levels, 47,48 although it may change insulin sensitivity. 49,50 On the other hand, surprisingly, inhibiting and exciting POMC neurons is related to an increase in glucose, 47,48 indicating that POMC neurons are involved in adapting glycemia to the time of the day. Since there are many different POMC neuronal subpopulations, 51,52 these observations indicate that a specific neuronal POMC population needs to be considered for analyzing neuronal inhibition or excitation by glucose.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, POMC neurons are glucose-excited neurons and play a role in the physiological control of systemic glucose homeostasis as exemplified by chemogenetic inhibition of POMC neurons decreasing glucose levels in normoglycemic animals ( 68 ). However, a more recent study revealed that selective activation of liver-innervating POMC neurons increases glucose concentrations ( 69 ). Thus, the role of POMC neurons in control of glucose homeostasis appears to be more complex and deserves future detailed studies.…”
Section: Pro-opiomelanocortin–expressing Neuronsmentioning
confidence: 99%